Contexts of changes in the habits in contemporary consumption: The pandemic and the crisis - Wardzała, Joanna; Patrzałek, Wanda (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
This paper examines the changes in consumption habits during the pandemic period as well as the impact of the crisis on young people’s consumption behavior. The study presents the considerations which are based on the authors’ own research, which involved the triangulation of qualitative and quantitative data. A quantitative study was conducted in 2021 on a representative sample of Poles (total number N = 1,268). This study aims to determine how much and to what extent the pandemic experiences have changed the consumer behavior habits of Poles. It was hypothetically assumed that the post-pandemic experiences had a significant impact on changing the consumption habits of Poles. In order to determine the durability of the changes in consumption that appeared in 2021, a qualitative research was carried out in 2023, in which a crisis in the consumption behavior of young people was conducted as an in-depth analysis. This research was conducted by the FGI (focus group interview) intelligence method among five focus groups. It assumed that young people are particularly sensitive to changes and they undertake compensatory consumption behavior during the crisis period.
Keywords: consumption habits; deconsumption; compensatory consumption; post-pandemic experience; compulsive consumption